Prevalence of Malaria Parasites among Tuberculosis Patients Attending Specialist Hospital, Gombe State, Nigeria - Attahiru Adamu; Bashir Abdulkadir; Mukhtar G.L (UMYU Journal of Microbiology Research)
Malaria and tuberculosis (TB) are two of the most prevalent endemic infections in Nigeria. Thus, a study on the co-infection of malaria parasites with tuberculosis was undertaken among patients attending State Specialist Hospital Gombe between November, 2010 and March, 2011. A total of 203 blood samples comprising of 103 samples from confirmed AFB-positive patients and 100 from AFB-negative patients (control) were collected and analysed for the presence of malarial parasites. All the samples were subjected to blood film using Giemsa Staining Technique and viewed under oil immersion Microscopy. The prevalence of malaria parasites among AFB- positive and negative patients were found to be 33% and 31% respectively. Malaria parasites were most prevalent among patients aged 41-64 years (39.0%). Male patients had the highest prevalence of 17.5%, while females had a prevalence rate of 15.5%. The higher prevalence reported may be of significance in the light of recent data, showing that malaria infection may exacerbate TB. Thus, adequate measures should be taken to free TB patients from malaria infection.